Cheedos Enterprise: dried chilies seed separator machine / Nurnazihah Zuhairi... [et al.] - Zuhairi, Nurnazihah; Razman, Siti Nur Shahirah; Isammudin, Farhah Balqis; Zulkifli, Aida Faridah; Samsudin, Filzah Najwa (2016)
Cheedos enterprise with slogan "the simple idea that can save your time" is a company which focuses on chilies seeds separator machine for home appliances.